Simulation Study on a Three-evaporator Air Conditioning System for Improved Humidity Control. (May 2017) - Yan, Huaxia; Deng, Shiming
Abstract: Multi-evaporator air conditioning (MEAC) may be regarded as one of the energy conscious air conditioning technologies. However, most MEAC systems currently focus on temperature control only, so that the potential of MEAC technology in achieving energy saving has not yet been fully explored. Therefore, in this paper, based on previous extensive related research by the investigators on modeling and controlling both single evaporator air conditioning (SEAC) systems and MEAC systems, a novel controller for a three evaporator air conditioning system will be developed. The novel controller was developed by integrating two previous control algorithms for a dual-evaporator air conditioning system for temperature control and for a SEAC system for improved indoor humidity control. Simulative controllability test results showed that, with the novel controller, improved control over indoor humidity levels could be obtained.